Biodiesel: uso, limitações e implicações técnicas devido à degradabilidade oxidativa - Pimenta Junior, Vicente Alves (2013)
Submitted by Vicente Alves Pimenta Junior (vicente.pimenta@delphi.com) on 2013-07-11T11:15:40Z No. of bitstreams: 1 Dissertação Vicente_final.pdf: 3937663 bytes, checksum: ce1db3ebf0d9f877a578d1520cb3083c (MD5) === Approved for entry into archive by Suzinei Teles Garcia Garcia (suzinei.garcia@fgv.br) on 2013-07-11T12:47:06Z (GMT) No. of bitstreams: 1 Dissertação Vicente_final.pdf: 3937663 bytes, checksum: ce1db3ebf0d9f877a578d1520cb3083c (MD5) === Made available in DSpace on 2013-07-11T12:57:26Z (GMT). No. of bitstreams: 1 Dissertação Vicente_final.pdf: 3937663 bytes, checksum: ce1db3ebf0d9f877a578d1520cb3083c (MD5) Previous issue date: 2013-06-18 === This study shows the special condition that the standby equipment (equipment that stays for long periods with no running) is submitted to, with biodiesel blends in its interior. It is shown that the validation tests to introduce the biodiesel in Brazil, made under the coordination of the Brazilian Government, were basically constituted of tests that generated mileage, as if the diesel universe were only composed of trucks, vans and buses. The off highway equipment in all forms of presentation and types of use, were not adequately covered in the validation study. The result is that a new fuel was introduced in the country (diesel and biodiesel blend), with the property of degradation a lot higher when compared to pure diesel. This paper presents the quality parameters required for a fuel in order to be considered appropriated; presents the main effects of oxidative degradation; makes a survey of best practices by the manufacturers of engines and diesel vehicles in the world, and finally enquire the fuel systems, engines and vehicles manufacturers in Brazil to understand if they warn their consumers and recommend to them preventive actions that are adapted to Brazilian conditions. In light of the problems observed in Brazil, few new procedures have to be made by the owners in order to have their equipment preserved. Among the recommendation the following stand out: a) the specification of the blend must be rigorously obeyed; b) wherever possible, when it is possible to forecast the stoppage of a machine, its tank has to be emptied; c) When the tank cannot be depleted, the fuel must be used or replaced within 30 days; d) Maybe re introduce, under special condition, pure diesel. This new reality that has been established with the introduction of biodiesel into the Brazilian energy matrix was not properly informed to the population. Emergency power generators that do not follow these recommendations may find problems to work due to fuel degradation in its interior and worst, people may realize this fact when the equipment is needed. === Este estudo apresenta a condição especial a que estão submetidos os equipamentos que ficam por longos períodos sem funcionar, sobretudo os chamados standby com misturas de biodiesel em seu interior. Mostra que os ensaios de validação para a introdução do biodiesel no Brasil, realizados sob o comando do governo brasileiro, foram basicamente constituídos por testes para acúmulo de quilometragem, como se o universo do diesel se resumisse a caminhões, vans e ônibus. Os equipamentos fora de estrada, em todas as suas formas de apresentação e uso, não foram adequadamente cobertos. O resultado é que um novo combustível foi introduzido no país (mescla de diesel mineral com biodiesel), com característica de degradabilidade muito maior do que o diesel puro. Este trabalho apresenta os parâmetros de qualidade necessários para que um combustível seja considerado adequado; apresenta os efeitos principais da degradação oxidativa; faz um levantamento das melhores práticas recomendadas pelos fabricantes de motores e veículos a diesel no mundo e, finalmente, consulta os fabricantes de sistema de injeção, motores e veículos no Brasil para saber se, em função das condições brasileiras, os fabricantes recomendam ações de prevenção distintas de suas matrizes. Em função dos problemas observados no país, algumas medidas adicionais precisam ser tomadas pelos proprietários de equipamentos a diesel para preservá-los. Dentre as medidas, destacam-se as seguintes: a) a especificação da mistura precisa ser obedecida com rigor; b) sempre que possível, quando o equipamento tiver de ser parado de modo previsível, o combustível deve ser esgotado do tanque; c) quando não for possível esgotar o tanque, o combustível tem de ser usado ou substituído em no máximo 30 dias; d) talvez reintroduzir sob condições especiais o diesel puro. Essa realidade nova que se instaurou com a introdução do biodiesel na matriz energética brasileira não foi devidamente informada à comunidade. Geradores de emergência que não seguem esses cuidados podem ter problemas para funcionar devido à degradação do combustível em seu interior e, pior, pode-se vir a descobrir esse fato apenas no momento da necessidade.